Współczesny przyrost ludności i możliwości rozwoju gospodarki światowej - Oryl, Kazimierz (Wydział Prawa i Administracji UAM, 1976)
The Author has stated that there are not existing essential obstacles for production growth which is necessary to meet the needs of the increasing population. It is true that the increasing world population causes many perturbations in economic growth. Those perturbations, however, result from political regimes and from the division of the world into underdeveloped and developed countries.
Present Population Growth and the Development Perspectives of the World Economy